Contamination trends and factors affecting the transfer of hexabromocyclododecane diastereomers, tetrabromobisphenol A, and 2, 4, 6-tribromophenol to breast milk in Japan. (June 2018) - Fujii, Yukiko; Kato, Yoshihisa; Masuda, Nanako; Harada, Kouji H.; Koizumi, Akio; Haraguchi, Koichi
Abstract: This study investigated contamination trends and factors affecting the levels of brominated flame retardants (BFRs), including hexabromocyclododecane (HBCD) diastereomers, tetrabromobisphenol A (TBBP-A), and 2, 4, 6-tribromophenol (2, 4, 6-TBP), in breast milk in Japan. Breast milk samples ( n = 64) were collected from mothers living in six prefectures in Japan. The mean concentrations were 2.2, 0.19, 0.29, 3.0, and 0.59 ng/g lipid weight for α-HBCD, β-HBCD, γ-HBCD, TBBP-A, and 2, 4, 6-TBP, respectively. Based on the previous studies, the levels of ΣHBCD in Japanese women's milk appear to be increasing, and the levels of TBBP-A are higher than those in other Asian countries. Although ΣHBCD were not correlated to phenolic BFRs, the concentration of β-HBCD was significantly correlated to the concentrations of TBBP-A ( r = 0.440, p < 0.01) and 2, 4, 6-TBP ( r = 0.320, p < 0.01). The concentration of γ-HBCD increased significantly with maternal age ( r = 0.378, p < 0.01), but the concentrations of the other analytes were not dependent on age. The concentration of α-HBCD was higher in primiparae than in multiparae ( p < 0.05), while TBBP-A was higher in multiparae. No significant correlation was found between the phenolic BFR levels in milk and mothers' age, working place, and drinking/smoking habits. These results suggest that exposure to α- and γ-HBCD diastereomers could be affected by maternal age and parity, respectively, because of their different kinetics and sources. Therefore, these factors should be considered when conducting infant risk assessments. Graphical abstract: Image 1 Highlights: Breast milk in Japan is analyzed for brominated flame retardants. α-Hexabromocyclododecane (HBCD) is the predominant HBCD diastereomer. There is a significant correlation between β-HBCD and tetrabromobisphenol A. The concentration of γ-HBCD increases significantly with maternal age. Maternal age and parity affect transfer of HBCD diastereomers into breast milk.